Algorithm design : foundations, analysis, and Internet examples - Goodrich, Michael T.; Tamassia, Roberto, 1960- (New York : Wiley, 2001)
Michael Goodrich and Roberto Tamassia, authors of the successful, Data Structures and Algorithms in Java, 2/e, have written Algorithm Engineering, a text designed to provide a comprehensive introduction to the design, implementation and analysis of computer algorithms and data structures from a modern perspective. This book offers theoretical analysis techniques as well as algorithmic design patterns and experimental methods for the engineering of algorithms. Market: Computer Scientists; Programmers
Includes bibliographical references (p. 689 - 697) and index.
eng
Keywords: Computer algorithms; Data structures (Computer science)